PENGARUH KOMUNIKASI INSTRUKSIONAL TERHADAP SIKAP SISWA MENGENAI BELAJAR KEWIRAUSAHAAN - fakhri (Jurnal Ilmiah Ekonomi Bisnis, 2020)
ABSTRACT The formulation of the problem compiled by the author is whether there is an effect of instructional communication on student attitudes about entrepreneurial learning either partially or simultaneously, also the authors formulate which variable is the most dominant of the independent variables on the dependent variable From the research results obtained by the regression equation as follows: Y = 0.739 + 0.382X1 + 0.461 X2 From these results can be interpreted: 1. The constant value is 0.739, it states that without the influence of the independent variables X1 (lecture) and X2 (teaching), the value of the dependent variable Y (student attitude) is 0.739. 2. The value of the regression coefficient of the independent variable X1 (lecture) is 0.382 The coefficient value means that if the value of the independent variable X1 is increased by one unit it will cause an increase in the value of the dependent variable Y (student attitude) of 0.382 units. In this case it is assumed that the value of the other independent variables is constant or zero. 3. The regression coefficient value of the independent variable X2 (teaching) is 0.461. The coefficient value means that if the value of the independent variable X2 is increased by one unit, it will cause an increase in the value of the dependent variable, namely Y (student attitude) of 0.461 units. In this case it is assumed that the value of the other independent variables is constant or zero. The coefficient value (R) is 0.624 or close to 1. It means that the relationship between the independent variables includes X1 X1 (lecture) and X2 (teaching) to the dependent variable, which is the attitude of students in the same direction. This means that if the independent variables which include X1 (lecture) and X2 (teaching) are increased, then the dependent variable is the attitude of students will also increase, and vice versa. The percentage of the effect of the independent variable on the dependent variable shown by the coefficient of simultaneous determination (R2) is 0.589 or 58.9%. This means that the rise and fall of the dependent variable that is the attitude of students is influenced by independent variables which include X1 (lecture) and X2 (teaching) of 58.9% and the remaining 41.1% is influenced by other variables outside this study. Keywords: Communication, instructional, student attitudes.